The impact of obstetric interventions and complications on women's satisfaction with childbirth a population based cohort study including 16,000 women - Maja Falk; Marie Nelson; Marie Blomberg (BMC, 2019)
Abstract Background As a quality marker and a tool for benchmarking between units, a visual analogue scale (VAS) (ranging from 1 to 10) to estimate woman's satisfaction with childbirth was introduced in 2014. This study aimed to assess how obstetric interventions and complications affected women's satisfaction with childbirth. Methods A retrospective cohort study including 16,775 women with an available VAS score who gave birth between January 2016 and December 2017. VAS score, maternal and obstetric characteristics were obtained from electronic medical records and crude and adjusted odds ratios (aOR) were calculated. Results The total prevalence of dissatisfaction with childbirth (VAS 1-3) was 5.7%. The main risk factors for dissatisfaction with childbirth were emergency cesarean section, aOR 3.98 95% confidence interval (CI) 3.27-4.86, postpartum hemorrhage ≥2000 ml, aOR 1.85 95%CI 1.24-2.76 and Apgar score < 7 at five minutes, aOR 2.95 95%CI 1.95-4.47. The amount of postpartum hemorrhage showed a dose-response relation to dissatisfaction with childbirth. Moreover, labor induction, instrumental vaginal delivery, and obstetric anal sphincter injury were significantly associated with women's dissatisfaction with childbirth. A total number of 4429/21204 (21%) women giving birth during the study period had missing values on VAS. A comparison of characteristics between women with and without a recorded VAS score was performed. There were statistically significant differences in maternal age and maternal BMI between the study population and excluded women due to missing values on VAS. Moreover, 64% of the women excluded were multiparas, compared to 59% in the study population. Conclusions Obstetric interventions and complications, including emergency cesareans section and postpartum hemorrhage, were significantly related to dissatisfaction with childbirth. Such events are common and awareness of these associations might lead to a more individualized care of women during and after childbirth.